2011
DOI: 10.1068/a43450
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Urban-Classified and Rural-Classified English Local Authority Areas

Abstract: This paper presents the results of an analysis of the Audit Commission's local quality-of-life indicators dataset to compare reported outcomes amongst 208 urban-classified and 144 rural-classified English local authority areas. We contextualise the demarcation of the urban and rural by reference to the transformational politics of the previous Labour government and its establishment of the sustainable communities initiative, whose controversial 'place-based' revitalisation essence continues to shape local gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This is perhaps surprising given the extensive research considering social deprivation and its experience across space (e.g. Campanera and Higgins, 2011;Cloke et al 1997;Huby et al, 2009;Phimister et al, 2000). 1 In the context of fuel poverty, an argument often raised in the policy debate is that rural households are disadvantaged due to the nature of rural housing stock and the more limited choice of energy available in rural areas.…”
Section: Introductionmentioning
confidence: 86%
“…This is perhaps surprising given the extensive research considering social deprivation and its experience across space (e.g. Campanera and Higgins, 2011;Cloke et al 1997;Huby et al, 2009;Phimister et al, 2000). 1 In the context of fuel poverty, an argument often raised in the policy debate is that rural households are disadvantaged due to the nature of rural housing stock and the more limited choice of energy available in rural areas.…”
Section: Introductionmentioning
confidence: 86%
“…In contrast, an objective quality of life assessment leads to varying results. For instance, Bertolini and Pagliacci (2017) and Campanera and Higgins (2011) pointed to a higher objective quality of life in rural spaces, while Ma et al (2020) showed comparable levels across urban and rural spaces. It should be noted, however, that these objective findings are always firmly linked to the country or region under study.…”
Section: Quality Of Life Differentiation In Urban and Rural Spacementioning
confidence: 95%
“…Studies of the spatial differentiation quality of life that simultaneously consider urban and rural spaces, and are carried out from the municipal to the regional level, often use data and products from national statistical offices (such as Bernini and Tampieri, 2017;Bertolini an Pagliacci, 2017;Székely 2006). Alternatively, data is gained from government commissions and organisations (Campanera and Higgins 2011) and specialised institutes (Gerdtham and Johannesson 2001). European data at the level of cohesion regions (Lenzi and Perucca 2018) and the level of countries measured by GDP (Shucksmith et al 2009; Sørensen 2014) are usually used.…”
Section: Quality Of Life Differentiation In Urban and Rural Spacementioning
confidence: 99%
See 1 more Smart Citation